Possibilities of Improving the Cluster Management System in Increasing the Competitiveness of the Region (Eurasian Journal of History, Geography and Economics, 2023)
Today, competition is the most important factor in all areas of the economy. The level of competitiveness of the region determines the well-being of its population. This article discusses the importance of the cluster management system and foreign experience in increasing the competitiveness of the region.